The resistant effect of SIRT1 in oxidative stress-induced senescence of rat nucleus pulposus cell is regulated by Akt-FoxO1 pathway. Issue 5 (10th May 2019) - He, Junsheng; Zhang, Ailiang; Song, Zhiwen; Guo, Shiwu; Chen, Yuwei; Liu, Zhiyuan; Zhang, Jinlong; Xu, Xu; Liu, Jinbo; Chu, Lei
Abstract : Objective: The senescence of nucleus pulposus (NP) cells induced by oxidative stress is one of the important causes of intervertebral disc degeneration (IDD). Herein, we investigated the role and action mechanism of silent information regulator 1 (SIRT1) in oxidative stress-induced senescence of rat NP cell. Methods: Premature senescence of rat NP cells was induced by sublethal concentration of hydrogen peroxide (H2 O2 ) (100 μM). SIRT1 was activated with SRT1720 (5 μM) to explore its effect on NP cells senescence. FoxO1 and Akt were inhibited by AS1842856 (0.2 μM) and MK-2206 (5 μM), respectively, to explore the role of Akt-FoxO1-SIRT1 axis in rat NP cells. Pretreatment with the resveratrol (20 μM), a common antioxidant and indirect activator of SIRT1, was done to investigate its role in senescent rat NP cells. Results: The mRNA and protein levels of SIRT1 were decreased in H2 O2 -induced senescent rat NP cells, and that specific activation of SIRT1 suppresses senescence. And the Akt-FoxO1 pathway, as the upstream of SIRT1, might be involved in the regulation of H2 O2 -induced senescence of rat NP cells by affecting the expression of SIRT1. In addition, the resveratrol played an anti-senescence role in rat NP cells, which might affect the Akt-FoxO1-SIRT1 axis. Conclusion: SIRT1 ameliorated oxidative stress-induced senescence of rat NP cell which was regulated by Akt-FoxO1 pathway, and resveratrol exerted anti-senescence effects by affecting this signaling axis.